Analisis Faktor Penyebab Audit Delay: (Studi Kasus Pada Perusahaan Jasa Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020) - Riswatul Hasanah; Sri Dwi Estiningrum (Owner : Riset dan Jurnal Akuntansi, 2022)
The study aimed to determine the effect of profitabilit and solvency on audit delay in financial services companies listed on the Indonesia Stock Exchange for the period 2019-2020. The study used a quantitative approach. The data collection tecnique was documentation, namely by collecting and recording the financial report of financial service companies listed on the Indonesia stock exchange for the period 2019-2020. The analysis technique used was multiple linier regressions. ANOVA the result showed that profitability and solvency owned simultaneous effect on audit delay.